Effects of cross-cultural adjustment on expatriates job performance in Emery Oleochemicals (M) Sdn. Bhd. / Nur Syazwani Najlaa Noordin and Siti Zulaikha Mokhtar - Noordin, Nur Syazwani Najlaa; Mokhtar, Siti Zulaikha (Faculty of Business and Management, 2014)
This research study has been conducted to identify the impact of cross-cultural adjustments on expatriate’s job performance in Malaysia. The main objective of this research is to find the most significant factors in cross-cultural adjustment on expatriate’s job performance. A conceptual framework comprises of four (4) factors which is cross-cultural training, organizational and family support, personality, and emotional intelligence are used to examined the impact of cross-cultural adjustments on expatriate’s job performance. The researchers have adopted the descriptive research to conduct the study on the issue raised. The researchers distributed 30 questionnaires among individual employees in Emery Oleochemicals (M) Sdn. Bhd as the method to acquire information needed. The researchers used Scientific Program of Social Science (SSPS) application. This application was used to obtain reliability test, the most significant factors, and the relationship between the variables. From the findings, it can be concluded that Cross-cultural Training as well as the Organizational and Family Support are the two factors that affected the expatriates’ job performance the most. It is because these two independent variables have significant relationship with the dependent variable.